Autentyzm a uczciwość. Zgodność czy rozbieżność? - Gryżenia SDB, ks. Kazimierz (Annales. Etyka w Życiu Gospodarczym, 2010)
Our contemporary life is said to be in conformity with what we do. People tend to be honest and trustworthy unlike those in the past - in the Victorian times, for example, when there were elements of hypocrisy and conventional behaviour among citizens. Many people nowadays live their lives according to their own subjective beliefs; and they speak openly about their both good and bad deeds – even if some of them were kept secret to the public. And the public is equally open to tolerate or even accept them.An analysis of many cases in which people follow their own moral beliefs shows that this category of people are not always honest – only then, when their system of moral values is in accord with the objective system of moral values. Individual moral beliefs can be a result of false or relative moral theories, or even constructed to fit one’s moral attitude. Behaviour in which one respects the established principles, though may seem genuine, does not need to be considered honest. Following this kind of thinking, a man does not have any motivation or need to control himself – human-beings can dispense with self-development. The Victorian hypocrite had at least a due respect for moral values and knew that he had done wrong. His honesty followed what was good in his life but his deeds were all in all doomed to failure. Failure on the way of applying the right moral principles in life is not dishonesty. Every attempt to follow them inspires humans to undertake some spiritual efforts and gives opportunity to one’s own personal development.